2000
DOI: 10.1089/clm.2000.18.67
|View full text |Cite
|
Sign up to set email alerts
|

Wound Healing of Animal and Human Body Sport and Traffic Accident Injuries Using Low-Level Laser Therapy Treatment: A Randomized Clinical Study of Seventy-Four Patients with Control Group

Abstract: In addition to accelerated wound healing, the main advantages of LLLT for postoperative sport- and traffic-related injuries include prevention of side effects of drugs, significantly accelerated functional recovery, earlier return to work, training and sport competition compared to the control group of patients, and cost benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
14

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 4 publications
2
39
0
14
Order By: Relevance
“…Such data corroborate the results from other authors who have used LILT during 12 days of tissue repair processes and verified responses from the fibroblastic cells and collagen molecules to the treatment 7,8,[19][20][21][22][23][24][25][26][27][28] . The types of activation ways proposed for the laser, take into account its action over the chromophores situated at the mitochondrias and cell membranes.…”
Section: Discussionsupporting
confidence: 90%
“…Such data corroborate the results from other authors who have used LILT during 12 days of tissue repair processes and verified responses from the fibroblastic cells and collagen molecules to the treatment 7,8,[19][20][21][22][23][24][25][26][27][28] . The types of activation ways proposed for the laser, take into account its action over the chromophores situated at the mitochondrias and cell membranes.…”
Section: Discussionsupporting
confidence: 90%
“…However, previous work has shown that both pain relief and enhanced wound healing can be initiated using direct and indirect LLLT effects on cellular activity. Direct cellular activation is postulated to lead to indirect activation of distant cells via secondary messengers (reactive oxygen species, lymphokines, cytokines, nitric oxide, and calcium) released by directly activated cells [12,34,35] . In this study, it was not possible to ascertain whether treatment of the nerves proximal to the wound site enhanced wound healing or alleviated potential discomfort at the wound site.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have demonstrated that lowlevel laser therapy (LLLT) stimulates wound healing, by increasing collagen deposition and blood flow in the wound area. [6][7][8][9][10][11][12][13] Some lasers, when used with the proper parameters, affect fibroblasts and collagen production in vitro, and promising results have been found utilizing the HeNe laser (632.8 nm) with multiple exposures. 9,[14][15][16][17][18][19] One effect of laser therapy (5 J/cm 2 ) is increased local blood flow in normal human skin of the sole of the foot.…”
Section: Introduction Dmentioning
confidence: 99%